Curriculum information management system and institutional knowledge - Díaz Pérez, Maidelyn; Armas Peña, Dayron; Rodríguez Font, Reinaldo J.; Carrillo-Calve, Humberto Andrés (Revista General de Información y Documentación, 2016)
The organization of knowledge in the context of Information Sciences has as essence the information and properly documented or recorded knowledge. The organization of knowledge as a process, involves both a physical description and the content of informational objects. And the product of that process is the descriptive representation of the attributes of an object or set of objects. The representations are constructed by language developed specifically for the purposes of the organization in information systems. Languages are divided into languages that describe the document (the media object) and languages that describe the information (content) .A From this premise the following general objective research analysis systems Institutional Information Management and Knowledge especially those who intend to use the Curriculum Vitae of the teacher as the sole source of information, measurement and representation of information and knowledge of an organization. The methodology applied empirical techniques used to analyze the theoretical and practical issues investigated trends. Within main results the importance of using personal curriculum as a source of reliable and standardized information is displayed; a summary of the main curricular systems that exist at the international and regional level; and graph data model case study (a system of information management and institutional knowledge with curricular approach); and finally, the proposed use of ontologies as the main tool for the semantic organization of information in a system of information and knowledge management of data and computing immediate viewing and representation of institutional knowledge.